Classicism and Romanticism in Finnish Architecture - William C. Miller (Oz, 1982)
In the opening lines of the Kalevala, the bard speaks of being ''From two widely sundered regions,'' where "Rarely can we meet together, Rarely can we meet the other." While the first canto of the Finnish national folk epic sets the stage for the ensuing poetic saga...